STRATEGIC MANAGEMENT PRACTICES IN MUSLIM SMES: THE ROLE OF AMANAH - Abd Rahman, Siti Syuhada (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
This study examines the role of amanah (trustworthiness), a core value in Islamic business ethics, in shaping the strategic management practices of Muslim-owned small and medium enterprises (SMEs) in Malaysia. While Muslim SMEs are central to Malaysia’s halal economy, empirical research examining how Islamic ethical values shape formal strategic management processes remains limited. Using a qualitative research design, semi-structured interviews were conducted with seven Muslim entrepreneurs selected through purposive sampling. The participants comprised Muslim owners of manufacturing firms in the Klang Valley who had more than ten years of business experience and remained actively involved in managing their enterprises. The data were analysed using an inductive thematic analysis supported by ATLAS.ti 9.0. The findings indicate that amanah underpins all phases of strategic management. In strategy formulation, entrepreneurs emphasised social responsibility, halal assurance, and the economic wellbeing of the Muslim community. During implementation, amanah was manifested through ethical business practices such as transparency, fairness, reliability, and fulfilment of promises. In the evaluation stage, amanah guided corrective actions that prioritised stakeholder interests over short-term financial gains. These findings extend strategic management theory by demonstrating how Islamic ethical values shape managerial decision-making and propose a values-based framework that contributes to the development of Islamic management scholarship. Practically, the study provides guidance for Muslim entrepreneurs on integrating amanah into strategic decision-making to strengthen ethical governance and promote sustainable business practices.